An Ecocentric Inspection of Frederick George Scott’s “The River” - Mr. A. Diwakar (International Journal of Scientific Research in Science and Technology, 2024)
Eco-criticism is a critical approach to literature which heaves light upon the relationship between human beings and physical environment. It is also known as ‘Green Literature’. This movement was initially started in America in 1980s, later emerged in the Great Britain in early 1990s. It examines how literature treats the subject of nature. There is a couple of important literary personalities associated with this Ecocriticism namely Cheryll Glotfelty and William Rueckert. Ecocriticism advocates the application of ecology and ecological concepts to the study of literature. It takes an earth centred approach to literary studies. It suggests that everything is connected with everything else. Ecocriticism is concerned with community, eco-system, population and biosphere etc. This research paper dissects Frederick George Scott’s poem “The River” with regard to an ecocritical outlook. F.G. Scott (Canadian poet) views the river itself as a living organism (Friend). The poem opens with the description of the topography of the little river, located in the Laurentians in northern Canada.
Keywords: Human beings; flora and fauna; Environment; Ecocriticism; Ecology; River; Topography; Eco friendliness